فتنة المتخيل وشبقية الجسد قراءة في رواية أنثى السراب لواسني الأعرج - توهامي, إيمان (قــــــراءات, 2019)
تقيم رواية أنثى السراب في لحظة تخيلية عالما موازيا للواقع في تقديما لتصويرها الجسد وتخييله  لكنه عالم مناقض له بحسب أنماط التخيل الواردة فيه، لكون الرواية منتوج خيالي ذو قاعدة اجتماعية يسعى فيها الفرد إلى تجاوز حدود واقعه المعتاد. بأن ينفلت منها مرة ويناقضها مرة أخرى، لكون المتخيل الروائي متدفق من المخيال العام الذي يعد مخزونا للتصورات والهواجس والرؤى والتوقعات حول الجسد في بعده التخيلي.   Abstract :   Entha sarabe novel mirage in a moment of imaginary parallel  world of reality in a presentation to be photographed the body and his imaginery; but contrary to his world of imagination, according to patterns contained therein, to the fact that the novel is a fictional social base where an individual seeks to go beyond the usual limits of reality product. To get out of them and contradicted once again, to the fact that the imaginary novelist jetted from the public imagination, which is the reservoir of perceptions and concerns and visions and expectations about the body in the imaginary beyond. What between reality and dream between fantasy and reality, emerges body to announce the renewal through  reverse of imagination and to take the significance embodied in which to become flesh legendary, shifts the body the natural reality to enter into the world of illusio the world of fantasy and imagination, out of the man unconscious and fancies